El conocimiento científico - Gomez del Río, María Eugenia; Ojeda, Susana; Piñero, María Teresa; Raffaeli, Adriana; Robledo, Federico; Sticca, María Alejandra; Vocos, María Teresa (2024)
Fil: Gomez del Río, María Eugenia. Universidad Nacional de Córdoba. Facultad de Derecho; Argentina.